Association of insulin sensitivity to lipids across the lifespan in people with Type 1 diabetes - Maahs, D. M. (2011)
AIMS: Insulin resistance and dyslipidaemia both increase cardiovascular risk in Type 1 diabetes. However, little data exist on the associations of insulin resistance to lipids in Type 1 diabetes. Our objective was to explore the associations between insulin resistance (assessed by glucose infusion rate) and lipids in people with Type 1 diabetes and determine whether adiposity and/or average glycaemia influence these associations. METHODS: Hyperinsulinaemic–euglycaemic clamp studies were performed in 60 subjects with Type 1 diabetes aged 12–19 years (age 15 ± 2 years, 57% female, duration of diabetes 6.3 ± 3.8 years, HbA(1c) 8.6 ± 1.5%) and 40 subjects with Type 1 diabetes aged 27–61 years (age 45 ± 9 years, 53% female, duration of diabetes 23 ± 8 years, HbA(1c) 7.5 ± 0.9%). Multiple linear regression models were fit to examine the association between glucose infusion rate and fasting lipid levels with adjustment for possible confounders. RESULTS: Lower glucose infusion rate was significantly associated with lower levels of HDL cholesterol in youths with Type 1 diabetes and with higher levels of triglycerides and higher triglyceride/HDL ratio in both youths and adults. The magnitude of the associations between glucose infusion rate and lipid levels translate into interquartile differences of 0.098 mmol/l for HDL cholesterol, 0.17 mmol/l for triglycerides and 1.06 for triglycerides/HDL in the adolescents and 0.20 mmol/l for triglycerides and 1.01 for triglycerides/HDL in the adults. The associations were attenuated and no longer statistically significant by adjustment for adiposity among adults, while adjustment for HbA(1c) had a small effect in youths and adults. CONCLUSIONS: Lower insulin sensitivity is associated with a more atherogenic lipid profile in both youths and adults with Type 1 diabetes.